ANALSIS KINERJA PENYULUHAN DALAM KEGIATAN PENYULUHAN USAHATANI KACANG PANJANG DI DESA ALEBO KECAMATAN KONDA - Dhita Syafitri; Iskandar Zainuddin Rela; Tjandra Buana (Universitas Halu Oleo, 2022)
The performance of agricultural extension workers is focused on solving problems faced by farmers, so that a good instructor's performance will have an impact on increasing farmers' performance in increasing their farming production. This study aims to determine the performance of extension workers in Alebo Village, Konda District. This study uses a quantitative descriptive method with 37 farmers as respondents. The results showed that the performance of the extension workers in Alebo Village in the implementation of agricultural extension was categorized as good, the performance of the extension officers in the preparation stage for the implementation of the extension with an average score of 134.5, the extension implementation stage was categorized as quite good with an average score of 109.1, while the performance of the extension workers on the evaluation and the reporting are categorized at a good level with an average score of 132.5.